Metrics for computing performance of data center for instigating Energy Efficient Data center - Shah, Asadullah (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2014)
Data centers now play an important role in modern IT infrastructures. Although much research efforts has been made in the filed of green computing, performance metrics for green data centers have been left ignored. This paper is devoted to identify and implement energy efficiency and green computing performance metrics in data centers. The metric helps data center managers to measure and implement cost and power saving in data centers. A metrics based energy efficient model for categorizing data center into measurable units is proposed which divides data center into four measurable areas and maps metrics to measure their efficiency and performance. The results generated after applying power usage effectiveness metrics clearly demonstrate poor performance of data center with PUE value of 3.5, which indicates very efficient data center.